Construção de um roteiro de apoio às aulas de eletricidade usando conceitos de economia doméstica de energia elétrica : configuração de um material potencialmente significativo - Barbosa, Paulo Mendes (2015)
This paper configures the construction of a support guide to electricity classes, using domestic economy concepts of electric power, trying to introduce electricity concepts nearest from the reality of students. The domestic electricity account was used as an anchor through measurement units, comparative bars charts of average consumption, the prices established by consumer groups and the flag system that took effect in 2015, to insert other electricity concepts, such as electric power, potential difference, electric charge, electric force and electric field, without restricting the use of mathematical language. At the same time, forms of electric power generation were worked, as well as the main sources in the country and in the world, and energy policies aimed at saving electricity in a sustainable way of life on our planet. This pedagogical work proposal considered the necessary conditions for meaningful learning to occur, emphasizing and exploring previous concepts. Considering that students learn in different ways, and each of them is unique and individual, the different types of intelligences and skills (skills added to talent), consolidated in multiple intelligences, were explored. This teaching sequence was configured in a 20-hour course, in which teaching and learning resources contextualized with the current reality were used, such as: (re)production of experiments both in virtual lab (simulators) and in teaching laboratory - simple inexpensive experiments and resolution of problem situations. In analysis and final considerations, obtained by classes notes, problem situations and questionnaires (before, during and after the course), concept maps, some changes were observed in the way students express physical concepts related to electricity, in speeches linked to their everyday life.